1999
DOI: 10.1007/s004250050531
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of cinnamyl alcohol dehydrogenase during defensive lignification in wheat ( Triticum aestivum L.): characterisation of the major inducible form

Abstract: The induction and substrate speci®city of cinnamyl alcohol dehydrogenase (CAD, EC 1.1.1.195) was investigated in relation to the deposition of a defensive, syringyl-rich lignin at wound margins in wheat (Triticum aestivum L. cv. Brigadier). Column chromatography of untreated, wounded and elicitor-treated tissues revealed three major CAD forms (CAD-A, -B and -C) of which only CAD-C was responsive to elicitors. Examination of the substrate preference of these fractions indicated p-coumaryl alcohol to be the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Similarly, Mitchell et al (1994Mitchell et al ( , 1999 reported on the induction of a sinapyl alcohol-specific CAD activity (SAD activity) in wheat leaves inoculated with spores of B. cinerea associated with the deposition of a syringyl-rich defence lignin.…”
Section: Elicitor-induced Transcriptional and Enzymatic Changes In Thmentioning
confidence: 96%
“…Similarly, Mitchell et al (1994Mitchell et al ( , 1999 reported on the induction of a sinapyl alcohol-specific CAD activity (SAD activity) in wheat leaves inoculated with spores of B. cinerea associated with the deposition of a syringyl-rich defence lignin.…”
Section: Elicitor-induced Transcriptional and Enzymatic Changes In Thmentioning
confidence: 96%
“…The PAL gene has been shown to be involved in defense signaling in tobacco and rice by its rapid induction in response to pathogens or an elicitor (Zhu et al, 1995;Shadle et al, 2003;Tanaka et al, 2003). This enzyme represents the entry point of the phenylpropanoid pathway for the synthesis of antimicrobial compounds, such as phytoalexins (Dixon, 2001), or of the lignin polymer, which can act as an inducible physical barrier against pathogen ingress (Mitchell et al, 1999). A rice phytoalexin, Sakuranetin, is synthesized through the phenylpropanoid pathway (Kodama et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…flavonoids, isoflavonoids, stilbenes, monolignols and lignans (Dixon 2001), or as physical barrier against pathogen infiltration e.g. the phenylpropanoid polymer: lignin (Boudet et al 1995;Mitchell et al 1999). Activation of PAL is considered as a marker for ongoing SAR in a plant.…”
Section: Biosynthesis Of C6c3mentioning
confidence: 99%